Расизмот и Фланери О’Конор: „Вештачкото црнчиште“ - Бужаровска, Румена (Институт за македонска литература, Скопје, 2020)
The ongoing Black Lives Matter protests following the murder of George Floyd in the USA in the spring of 2020 invigorated a 25-year-old debate on the issue of race and Flannery O’Connor. This debate, triggered by an article in the New Yorker, caused a stir to “cancel” Flannery O’Connor. In the light of her being published in Macedonian for the first time this fall, I have attempted to analyze her contested and controversial short story “The Artificial Nigger” by taking into account the issue of race. My analysis aims to show that O’Connor’s intention and overall ethos of the story is undoubtedly anti-racist, serving to criticize racism in the segregated South through the ridicule of the white characters in the story. However, I also take into account O’Connor’s dominantly white perspective that reduces the black characters to tropes. Finally, I conclude that removing Flannery O’Connor’s work out its historical and social context wrongly diminishes her value and robs the readers of her narrative genius.
Keywords: Американски југ, расизам, Фланери О’Конор, култура на исклучување, „Вештачкото црнчиште“, American South, racism, Flannery O’Connor, cancel culture, “The Artificial Nigger”